2023
DOI: 10.1038/s41598-023-28299-4
|View full text |Cite
|
Sign up to set email alerts
|

Resonant laser ionization and mass separation of 225Ac

Abstract: Abstract$$^{225}$$ 225 Ac is a radio-isotope that can be linked to biological vector molecules to treat certain distributed cancers using targeted alpha therapy. However, developing $$^{225}$$ 225 Ac-labelled radiopharmaceuticals remains a challenge due to the supply shortage of pure $$^{225}$$ … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
14
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(14 citation statements)
references
References 56 publications
0
14
0
Order By: Relevance
“…Furthermore, the maximal extraction efficiency of actinium from this work was established as 2.1(6)%. This efficiency can be improved by changing the laser ionization scheme 29 . The maximal extraction efficiency of Ra and Fr was established as 13.8(25)% and 101(35)% respectively, in line with expectations based on their chemical nature.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, the maximal extraction efficiency of actinium from this work was established as 2.1(6)%. This efficiency can be improved by changing the laser ionization scheme 29 . The maximal extraction efficiency of Ra and Fr was established as 13.8(25)% and 101(35)% respectively, in line with expectations based on their chemical nature.…”
Section: Discussionmentioning
confidence: 99%
“…Research of Ac-225 radiopharmaceuticals is a promising direction for the development of more effective therapy with alpha emitters having far fewer side effects and fewer discomforts (Harvey, 2018;Price & Orvig, 2014;Ramogida & Orvig, 2013). While numerous clinical trials have shown that Ac-225 radiopharmaceuticals have the ability to treat advanced malignancies, (Chatterjee et al, 2023;Hope et al, 2023;Johnson et al, 2023;Li, Chyan, et al, 2021). As new agents receive FDA approval and expenses are covered by insurance coverage, the future of radio-theranostics is bright.…”
Section: Discussionmentioning
confidence: 99%
“…Actinium is the first element in the actinide series, and only its two naturally occurring isotopes, 228 Ac and 227 Ac, are found in the decay chains of 232 Th and 235 U, respectively. The most common isotope, 227 Ac, has a long half‐life of 21.7 years and decays primarily by β‐emissions (Johnson et al, 2023). A β‐emitter that is also exceptionally rare is 228 Ac.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…From this analysis we obtained maximal extraction efficiency of Ac equal to 2.1(6)%. At the offline CERN MEDICIS facility, laser ionization of actinium originating from an actinium nitrate mass marker deposited on a rhenium surface and on a ThO 2 matrix reached 15.1(6)% 30 . The conditions were substantially different between those offline measurements and the experiment reported here, in particular the absence of diffusion through the target material.…”
Section: Release Curves and Yieldsmentioning
confidence: 99%